6
$\begingroup$

When does $a^2+b^2 = c^3 +d^3$ for all integer values $(a, b, c, d) \ge 0$. I believe this only happens when: $a^2 = c^3 = e^6$ and $b^2 = d^3 = f^6$. With the following exception:

  • $1^3+2^3 = 3^2 + 0^2$

Would that statement be correct?

Is there a general formula for when this happens?

$\endgroup$
  • 1
    $\begingroup$ A small amount of trial and error gives $27^2+72^2=10^3+17^3$. I suspect there will be many solutions. $\endgroup$ – David Jun 26 '14 at 1:08
  • 2
    $\begingroup$ If you allow zero, there are definitely lots more possibilities. Set $a=b$, and $d=0$. Then you want to solve $2b^2=c^3$. Make $b$ and $c$ powers of $2$, so that you end up with $2^{1+2k}=2^{3m}$ for some integers $k,m$. Now you just need to solve $1+2k=3m$, which has an infinite number of positive solutions (because 2 and 3 are relatively prime). $\endgroup$ – process91 Jun 26 '14 at 1:11
  • 5
    $\begingroup$ An integer $n$ is the sum of two squares if and only if the following condition holds: $n$ does not have any prime factor $p=4k+3$ to an odd power. You could try to find out when this happens for $n=c^3+d^3$. I believe the smallest solution, other than the ones you mentioned, is $4^2+7^2=1^3+4^3$. $\endgroup$ – David Jun 26 '14 at 1:12
  • 1
    $\begingroup$ There is, I think, no simple criterion for an integer to be a sum of two cubes, so it's unlikely that there will be "a general formula for when this happens". $\endgroup$ – Gerry Myerson Jun 26 '14 at 1:40
  • 1
    $\begingroup$ A possible approach to prove that there is an infinite family of non-trivial solution is to find an algebraic identity like $$(ax^2+bx+c)^3+(dx^2+ex+f)^3=(gx^3+hx^2+ix+j)^2+(kx^3+lx^2+mx+n)^2.$$ It may happen that $a^3+d^3=g^2+k^2$ and $c^3+f^3=j^2+n^2$ lead to a new non-trivial solution by Vieta jumping. $\endgroup$ – Jack D'Aurizio Jun 26 '14 at 2:50
5
$\begingroup$

Equation:

$$x^2+y^2=z^3+u^3$$

Formula of the solution, you can write:

$$x=q^6-2(a+s+t)q^5+(t^2-2(4a+3s)t-3a^2-10as-s^2)q^4-$$ $$-4(3t^3+(5a+4s)t^2+(3a^2+2as+s^2)t+a(a^2-s^2))q^3+$$ $$+(7t^4+4(a+s)t^3+6(3a^2+2as+s^2)t^2+4(3a^3+9sa^2+3as^2-s^3)t+3a^4+12sa^3+$$ $$+18s^2a^2-4as^3-s^4)q^2-(t^2-2ts+a^2-2as-s^2)(10t^3+18(a+s)t^2+$$ $$+2(5a^2+8as+5s^2)t+2(a^3+sa^2+as^2+s^3))q+(t^2-2at-a^2-2as+s^2)(7t^4+$$ $$+10(a+s)t^3+8(a^2+as+s^2)t^2+2(a^3+sa^2+as^2+s^3)t+a^4+2a^2s^2+s^4)$$

$$..............................................................$$

$$y=q^6+2(a+s+t)q^5+(t^2-2(3a+4s)t-a^2-10as-3s^2)q^4+$$ $$+4(3t^3+(4a+5s)t^2+(a^2+2as+3s^2)t+s(s^2-a^2))q^3+$$ $$+(7t^4+4(a+s)t^3+6(a^2+2as+3s^2)t^2+4(-a^3+3sa^2+9as^2+3s^3)t-a^4-4sa^3+$$ $$+18a^2s^2+12as^3+3s^4)q^2+(t^2-2at-a^2-2as+s^2)(10t^3+18(a+s)t^2+$$ $$+2(5a^2+8as+5s^2)t+2(a^3+sa^2+as^2+s^3))q+(t^2-2ts+a^2-2as-s^2)(7t^4+$$ $$+10(a+s)t^3+8(a^2+as+s^2)t^2+2(a^3+sa^2+as^2+s^3)t+a^4+2a^2s^2+s^4)$$

$$.............................................................$$

$$z=q^4-2(t^2+a^2+s^2+4at+4as+4st)q^2-3t^4-8(a+s)t^3-$$ $$-2(a^2+4as+s^2)t^2+a^4+2a^2s^2+s^4$$

$$..............................................................$$

$$u=(q^2+t^2+a^2+s^2)(q^2+5t^2+4(a+s)t+a^2+s^2)$$

$q,a,s,t$ - integers of any sign.

After substitution and obtain numerical results. It should be divided into common divisor. To get a primitive solution.

$\endgroup$
3
$\begingroup$
  1. $a=x^3-3x^2y-3xy^2+y^3,b=x^3+3x^2y-3xy^2-y^3,c=d=x^2+y^2.$

  2. $a=3(x^3-3xy^2),b=3(3x^2y-y^3),c=x^2+y^2,d=2(x^2+y^2)$

    $\cdots$

See this post.

$\endgroup$
  • $\begingroup$ And how to be with relatively Prime numbers? Is there still a mutually simple solutions. $\endgroup$ – individ Jun 26 '14 at 4:37
2
$\begingroup$

Let $c=x^2,d=y^2,i=\sqrt{-1}$, then $$c^3+d^3=x^6+y^6=(x^3-(yi)^3)(x^3+(yi)^3)\\ =(x-yi)(x^2+xyi-y^2)(x+yi)(x^2-xyi-y^2)$$

Let $a+bi=(x-yi)(x^2-xyi-y^2),a-bi=(x+yi)(x^2+xyi-y^2)$, then $a^2+b^2=c^3+d^3$.

We get $a=x^3-2xy^2,b=y^3-2x^2y,c=x^2,d=y^2.$

If $a<0$ or $b<0$, we can take the absolute value.

For example, let $x=1,y=2$ we get $a=-7,b=4,c=1,d=4$ hence $7^2+4^2=1^3+4^3,$

let $x=3,y=2,$ we get $a=3,b=-28,c=9,d=4$ hence $3^2+28^2=9^3+4^3.$

$\endgroup$
  • $\begingroup$ But what if not the squares? $\endgroup$ – individ Jun 26 '14 at 6:57
  • $\begingroup$ You get a private decision. The formula in General has a bulky look. $\endgroup$ – individ Jun 26 '14 at 6:59
0
$\begingroup$

Not really natural to demand both cubes positive...

           1           1           2 = 2
           1           0           1 =  1 
           2           2          16 = 2^4
           2           1           9 = 3^2
           2           0           8 = 2^3
           3          -1          26 = 2 * 13
           4           4         128 = 2^7
           4           2          72 = 2^3 * 3^2
           4           1          65 = 5 * 13
           4           0          64 = 2^6
           4          -3          37 = 37
           5           5         250 = 2 * 5^3
           5           0         125 = 5^3
           5          -2         117 = 3^2 * 13
           5          -3          98 = 2 * 7^2
           5          -4          61 = 61
           6          -2         208 = 2^4 * 13
           7           5         468 = 2^2 * 3^2 * 13
           7           3         370 = 2 * 5 * 37
           7          -5         218 = 2 * 109
           8           8        1024 = 2^10
           8           5         637 = 7^2 * 13
           8           4         576 = 2^6 * 3^2
           8           2         520 = 2^3 * 5 * 13
           8           0         512 = 2^9
           8          -3         485 = 5 * 97
           8          -6         296 = 2^3 * 37
           8          -7         169 = 13^2
           9           9        1458 = 2 * 3^6
           9           8        1241 = 17 * 73
           9           4         793 = 13 * 61
           9           1         730 = 2 * 5 * 73
           9           0         729 = 3^6
           9          -7         386 = 2 * 193
          10          10        2000 = 2^4 * 5^3
          10           5        1125 = 3^2 * 5^3
          10           0        1000 = 2^3 * 5^3
          10          -4         936 = 2^3 * 3^2 * 13
          10          -6         784 = 2^4 * 7^2
          10          -7         657 = 3^2 * 73
          10          -8         488 = 2^3 * 61
          11           1        1332 = 2^2 * 3^2 * 37
          12           5        1853 = 17 * 109
          12          -4        1664 = 2^7 * 13
          12          -7        1385 = 5 * 277
          12         -11         397 = 397
          13          13        4394 = 2 * 13^3
          13          12        3925 = 5^2 * 157
          13          11        3528 = 2^3 * 3^2 * 7^2
          13           2        2205 = 3^2 * 5 * 7^2
          13           0        2197 = 13^3
          13          -1        2196 = 2^2 * 3^2 * 61
          13          -8        1685 = 5 * 337
          13         -11         866 = 2 * 433
          14          13        4941 = 3^4 * 61
          14          10        3744 = 2^5 * 3^2 * 13
          14           6        2960 = 2^4 * 5 * 37
          14           1        2745 = 3^2 * 5 * 61
          14          -7        2401 = 7^4
          14         -10        1744 = 2^4 * 109
          14         -11        1413 = 3^2 * 157
          15          11        4706 = 2 * 13 * 181
          15          -5        3250 = 2 * 5^3 * 13
          16          16        8192 = 2^13
          16          10        5096 = 2^3 * 7^2 * 13
          16           9        4825 = 5^2 * 193
          16           8        4608 = 2^9 * 3^2
          16           4        4160 = 2^6 * 5 * 13
          16           1        4097 = 17 * 241
          16           0        4096 = 2^12
          16          -3        4069 = 13 * 313
          16          -6        3880 = 2^3 * 5 * 97
          16         -12        2368 = 2^6 * 37
          16         -14        1352 = 2^3 * 13^2
          17          17        9826 = 2 * 17^3
          17          12        6641 = 29 * 229
          17          10        5913 = 3^4 * 73
          17           7        5256 = 2^3 * 3^2 * 73
          17           0        4913 = 17^3
          17          -2        4905 = 3^2 * 5 * 109
          17          -4        4849 = 13 * 373
          17          -7        4570 = 2 * 5 * 457
          17         -12        3185 = 5 * 7^2 * 13
          17         -14        2169 = 3^2 * 241
          17         -15        1538 = 2 * 769
          18          18       11664 = 2^4 * 3^6
          18          16        9928 = 2^3 * 17 * 73
          18           9        6561 = 3^8
          18           8        6344 = 2^3 * 13 * 61
          18           2        5840 = 2^4 * 5 * 73
          18           0        5832 = 2^3 * 3^6
          18         -14        3088 = 2^4 * 193
          19           7        7202 = 2 * 13 * 277
          19           5        6984 = 2^3 * 3^2 * 97
          19          -7        6516 = 2^2 * 3^2 * 181
          19          -9        6130 = 2 * 5 * 613
          20          20       16000 = 2^7 * 5^3
          20          17       12913 = 37 * 349
          20          10        9000 = 2^3 * 3^2 * 5^3
          20           5        8125 = 5^4 * 13
          20           0        8000 = 2^6 * 5^3
          20          -8        7488 = 2^6 * 3^2 * 13
          20         -12        6272 = 2^7 * 7^2
          20         -14        5256 = 2^3 * 3^2 * 73
          20         -15        4625 = 5^3 * 37
          20         -16        3904 = 2^6 * 61
jagy@phobeusjunior:~$ 

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.